Trend Paradigma dalam Pendidikan Matematika - Andes Safarandes Asmara; Iwan Junaedi (Scholaria: Jurnal Pendidikan dan Kebudayaan, 2018)
The current mathematics education is the fruit of past educational debates. First, we examine the past attempts to change the way mathematics is being taught and argue that education is always based on a traditional paradigm. Next try to explain the emergence of a new paradigm that grew out of a combination of theories from cognitive psychology, awareness of the importance of culture for learning, and the belief that students must get meaningful learning. This article discusses theories about paradigms that underlie the learning theory in general education, especially mathematics education. These paradigms include behaviourism, constructivism, critical theory, cognition theory. We discuss some of the implications of this reform related to how mathematics educators might work with math teachers.